SATISFACTION-BASED PATIENT LOYALTY ANTECEDENT MODEL AT CUT MUTIA HOSPITAL - Adnan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to determine the effect of brand image and service quality on patient loyalty with patient satisfaction as an intervening variable (study of the North Aceh Cut Meutia Hospital Agency. The data used are primary data sourced from the distribution of questionnaires to 150 patients who seek treatment at home Cut Meutia Hospital North Aceh Analysis of data using Structural Equation Modeling (SEM) The results of data analysis found that brand image variables influence patient satisfaction and patient loyalty while service quality variables affect patient satisfaction but do not affect patient loyalty as well as satisfaction variables the patient is not a variable that mediates the quality of service to patient loyalty at the North Aceh Cut Meutia Hospital Agency.